2016
DOI: 10.1038/srep36227
|View full text |Cite
|
Sign up to set email alerts
|

Identifying reproducible cancer-associated highly expressed genes with important functional significances using multiple datasets

Abstract: Identifying differentially expressed (DE) genes between cancer and normal tissues is of basic importance for studying cancer mechanisms. However, current methods, such as the commonly used Significance Analysis of Microarrays (SAM), are biased to genes with low expression levels. Recently, we proposed an algorithm, named the pairwise difference (PD) algorithm, to identify highly expressed DE genes based on reproducibility evaluation of top-ranked expression differences between paired technical replicates of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Because Student's t-test biases towards genes with low expression levels in small size samples, i.e. the cancer cell line datasets here, the reproducibility-based pairwise difference (PD) [31,32] was combined to detect DEGs between the treatment group and the control group of the cell line datasets. It has been demonstrated that the PD algorithm could identify many DEGs with high expressions in small-scale cancer cell line datasets which tended to be missed by Student's t-test.…”
Section: Identification Of Degsmentioning
confidence: 99%
“…Because Student's t-test biases towards genes with low expression levels in small size samples, i.e. the cancer cell line datasets here, the reproducibility-based pairwise difference (PD) [31,32] was combined to detect DEGs between the treatment group and the control group of the cell line datasets. It has been demonstrated that the PD algorithm could identify many DEGs with high expressions in small-scale cancer cell line datasets which tended to be missed by Student's t-test.…”
Section: Identification Of Degsmentioning
confidence: 99%